Advances in natural-product-based nanomaterials for treatment of acute lung injury - Yang, Jiajing; Hsu, Yenna; Liu, Rui; Chen, Dan; Zhou, Zhihang; Zou, Jingshan; Xiong, Peizheng; Zhou, Li (Frontiers in Bioengineering and Biotechnology, 2025)
Acute lung injury (ALI) is a critical condition characterized by rapid-onset lung inflammation, often resulting in respiratory distress. Current treatments are mainly based on glucocorticoids, but side effects and variable efficacy limit their effectiveness. This has prompted research into novel treatments, focusing on natural-product-based nanomaterials (NP-NMs), which offer a promising alternative. NP-NMs, synthesized from biological sources such as plants and microorganisms, have shown potential in therapy of ALI by enhancing drug delivery, reducing systemic side effects, and modulating inflammation. This review summarizes the latest research on NP-NMs, highlights their advantages in terms of biocompatibility, targeted delivery, and overcoming biologic barriers, and explores the challenges of developing NP-NMs in terms of standardized synthesis methods, comprehensive toxicological evaluation, and optimization for clinical translation. The significance of this review is to provide ideas for the development of more effective treatments for ALI, supporting further investigation into their clinical applicability.